The Impact of Workers Productivity Under Simulated Environmental Factor by Taguchi Analysis - Ahmad Rasdan, Ismail; Che Mohammad Nizam, Che Kamaruddin; Mohd Hanifiah, Mohd Haniff; Baba, Md Deros (Elsevier, 2014)
The objective of this study is to determine the dominance impact of environmental factors such as illuminance, humidity and temperature on worker productivity by Taguchi Method. A study was conducted under simulated environment factor which examined were the illuminance, humidity and temperature of the surrounding workstation area in the closed simulation lab. A set of representative data including the illuminance, humidity and temperature level and production rate were collected during the study. The production rate data were collected through observations and survey questionnaires while the illuminance, humidity and temperature level measured by valid apparatus and equipment. The Taguchi method was utilized to find the sequence of dominant factors that contributed to the productivity of the operator at that specified production workstation. The study reveals that the dominant factor that contributed to the productivity was temperature followed by illuminance and relative humidity.